The Abuse of Power in the Alleged Covid-19 Polymerase Chain Reaction Test Business: Criminal Aspects - Dwi Cahyani, Tinuk; Kurniawan, Wahyudi; Al-Fatih, Sholahuddin (KnE Social Sciences, 2022)
The abuse of power during the Covid-19 pandemic was felt to be very massive by the governmentbecause the health sector received far more attention than others. The Covid-19 test was made mandatory to travel in spite of it being very expensive for the community, and various news spread in the community made suspicion of abuse of power. By using qualitative methods and Nvivo 12 Plus to map the data, this research was conducted to determine whether the abuse of power actually occurred. The results of the study show that the cases that occur are too subjective to be considered an abuse of power, in this case, the government and corporations are also working according to the needs of the community to overcome the Covid-19 pandemic. However, to see the disadvantages of this, the author feels that further research is still needed regarding the urgency of the Covid-19 test while traveling and its impact on state budget losses. Keywords: abuse of power, pandemic, Covid-19 test, corporations